Enhancing students' cognitive ability on Newton laws through the integrated SSCS-TPACK learning model - Lissa Zikriana; Sharfina Sharfina; Khairunnisak Khairunnisak; Nanda Safarati (International Journal on Education Insight, 2026)
This study aims to determine the effectiveness of the integrated SSCS-TPACK model, a model which integrates search-solve-create-share framework and technological-pedagogical content knowledge, in improving students’ cognitive abilities regarding Newton’s laws. In this study, effectiveness is operationally defined as a statistically significant increase in students’ cognitive ability scores following the implementation of this learning model. This study employed a one-group pretest–posttest design involving 30 eighth-grade students from SMP Negeri 3 Peusangan, a public junior high school in Peusangan, Aceh, Indonesia. Participants were selected using a random sampling technique. Data were analyzed using a paired t-test. The results showed a statistically significant difference between pretest and posttest scores (t = 29.08, p < 0.001), indicating that students’ cognitive abilities improved after learning with the integrated SSCS-TPACK model. These findings suggest that the integrated SSCS-TPACK model is effective in improving students’ cognitive abilities in learning Newton’s laws and therefore can serve as an alternative technology-integrated teaching approach to enhance the physics learning process.